Les formateurs d'enseignants face aux environnements personnels d'apprentissage de leurs étudiants : représentations et accompagnement - Nicolas Roland; Sophie Vanmeerhaeghe
The integration and use of technologies for pedagogical purposes are, with a few exceptions, not really present in the training of the future primary and secondary school teachers. Nowadays, though, the teaching profession is more and more complex and requires the mastery of those technologies, whether it is to teach or to accompany the students in their use of digital technologies. Moreover, the students - and future teachers - resort to digital tools and services in order to create or to organize their personal learning environment (PLE). However, many studies show that those students don't have the skills needed to optimally manage this environment. Therefore, when they enter higher education, they need a pedagogical help and support in order to choose appropriate tools to reach their learning objectives. Through a questionnaire survey, this study aims to determine the representations of the « teachers' instructors » concerning their students' PLE, as well as to have a look at the pedagogical approaches they implement to accompany their students in the production of PLE. This paper offers a first inventory that allows understanding what the PLE of their students mean to them and how they help their students preparing those PLE.